STRATEGI MARKETING MIX SYARIAH UNTUK BISNIS ONLINE DALAM MENINGKATKAN PENJUALAN PADA LUMINTU MUKENA GROSIR TULUNGAGUNG - Rinawati, Yuni -; Zahro, Nuril Amirotus; Sujianto, Agus Eko (Universitas Muhammadiyah Surabaya, 2023)
This study aims to determine the application of sharia marketing mix at Lumintu Mukena Grosir Tulungagung in increasing sales. The research approach used is qualitative with deep interviews and case study research types. Data is sourced from interviews, observations and documentation. The results of this study show that the application of sharia marketing mix at Lumintu Mukena Grosir Tulungagung consists of 4p, namely (1) Product, where the product is made from harmless materials, prioritizes quality, includes special characteristics on the product, namely with manual embroidery and there is no element of fraud because the product sent is in accordance with the image listed on the sales media. (2) Price, where the price of the product adjusts to the quality of the product sold or ordered by the customer such as in terms of the type of fabric, size, model, motif, to color. (3) Place or distribution, where the distribution is carried out using a trusted shipping service and in keeping the goods in good condition, packaging is considered in such a way. (4) Promotion, in promoting its products is carried out through social networks such as, Whatsaap, Facebook, and Shopee, where this promotion adjusts to the conditions of the product.